Budaya Organisasi dan Faktor-Faktor yang Membentuknya di Sekolah - Khairunnisa Khairunnisa; Putri Fadila Batubara; Aisyah Hafizha; Akhmad Mukhlasin (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research aims to explore organizational culture and identify its shaping factors in the context of an educational environment. By adopting a case study approach, this research offers an in-depth analysis of the dynamics of organizational culture in a private educational institution in Medan. The research methodology relies on data triangulation through in-depth interviews, direct observation and document review. Thematic analysis was used to process the collected data, enabling a holistic understanding of the phenomenon under study. The research findings revealed that the concept of organizational culture in a school environment is a manifestation of a system of values, beliefs, and patterns of behavior that are collectively embraced by all elements of the school. This study successfully identified several main factors that play a role in the formation of the organizational culture, including: the leadership style of the principal, the individual characteristics of the teachers, the prevailing education policy, and the expectations of the parents. In conclusion, organizational culture in a school environment is formed through a complex interaction of various factors. A deep understanding of these factors can serve as a foundation for educational institutions in their efforts to manage and develop a conducive organizational culture. This in turn is expected to encourage the improvement of learning quality as well as the professional development of educators.